The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4103/0366-6999.193447
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Dysfunction in Sepsis

Abstract: Objective:Sepsis is defined as life-threatening organ dysfunction due to a dysregulated host response to infection. In this article, we reviewed the correlation between neutrophil dysfunction and sepsis.Data Sources:Articles published up to May 31, 2016, were selected from the PubMed databases, with the keywords of “neutrophil function”, “neutrophil dysfunction”, and “sepsis”.Study Selection:Articles were obtained and reviewed to analyze the neutrophil function in infection and neutrophil dysfunction in sepsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 40 publications
1
30
0
2
Order By: Relevance
“…Similar findings were seen in a previous study investigating the directional migration speed of isolated neutrophils following burn injury [ 20 ]. One explanation for the observed decrease in neutrophil migration abilities is that high levels of circulating proinflammatory cytokines early in sepsis increase levels of inducible nitric oxide which in turn may decrease neutrophil adhesion and transmigration to inflammatory sites [ 21 , 22 ]. Additionally, it has been shown that there is a significant increase in rigidity of neutrophils isolated from septic patients compared to normal controls [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were seen in a previous study investigating the directional migration speed of isolated neutrophils following burn injury [ 20 ]. One explanation for the observed decrease in neutrophil migration abilities is that high levels of circulating proinflammatory cytokines early in sepsis increase levels of inducible nitric oxide which in turn may decrease neutrophil adhesion and transmigration to inflammatory sites [ 21 , 22 ]. Additionally, it has been shown that there is a significant increase in rigidity of neutrophils isolated from septic patients compared to normal controls [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The duration and degree of neutropenia underscored the increased risk of life-threatening infections. [ 14 ] Fever and neutropenia are common in patients with hematologic malignancies during chemotherapy, and approximately 10–30% of patients experience sepsis. [ 15 ] Severe neutropenia is a risk factor for an infection that occurs in acute leukemia after chemotherapy and is an important factor that affects the prognosis of infection.…”
Section: Discussionmentioning
confidence: 99%
“…While this model did not directly use bacterial challenge, it employed mixtures of cytokines important for sepsis in humans, which is defined as "life-threatening organ dysfunction caused by a dysregulated host response to infection" [70], in which neutrophilic inflammation is an important component [71]. Another antimicrobial mechanism involves the release of histone-bound DNA complexed with primary granule proteins, such as NE and myeloperoxidase (MPO), in the form of NETs [72].…”
Section: Bacterial Infectionsmentioning
confidence: 99%